A Security Level Comparison of Caesar cipher, Columnar Transposition cipher and Row Transposition cipher in Tamil Messages - VEERASINGAM, VIMALESWARI; HARUN, NUR ZIADAH (Applied Information Technology And Computer Science, 2023)
Cryptography is a technique that effectively implements privacy and protects confidential information delivered via insecure channels of communication. To present-day, no research has been done to encrypt Tamil letters using the Caesar cipher and Columnar Transposition cipher, and Row Transposition cipher to compare the security level. This research aims to propose a security analysis of the Caesar cipher, and Row Transposition cipher in the Tamil language. To examine the security level of the ciphers, a cryptanalysis experiment was carried out using the Java program. The result will be evaluated the best cipher for the Tamil language through the performance of the ciphers by comparing the complexity of the ciphers to crack the ciphertext using the number of possibilities to crack the cipher and the time taken to crack it. The proposed enhancement is expected to secure communication between people who uses the Tamil Language in their life by providing confidentiality of the information.